ANALISIS TINGKAT PEMBAYARAN UPAH DAN HAK PEKERJA YANG DITERIMA TENAGA KERJA PERUSAHAAN OUTSOURCING PT JAWARI SENTOSA, TUALANG, KABUPATEN SIAK - Suseno Aji Suryana; Meyzi Heriyanto, (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research aims to know the level of payment of wages and workers’ rights received of labour outsourcing company PT Jawari Sentosa, Tualang, District Siak, under the provisions of the legislation in force, namely the Minister Regulation of Labour No. PER-01/MEN/1999 about Minimum Wage and the Law No. 13 of 2003 about Employment. This research took a number of respondents as many as 61 people.Data were obtained through questionnaires and interviews with key informance then further processed to be tested by the Minister Regulation of Labour No. PER-01/MEN/1999 about Minimum Wage and the Law No. 13 of 2003 about Employment. So we can see the level of the payment of wages and workers’ rights received of labour outsourcing company PT Jawari Sentosa, Tualang, District Siak in accordance with the provisions of laws and regulations that are applicable.The results showed that the company has not fully implement policies regarding the payment of wages by the Minister Regulation of Labour No. PER-01/MEN/1999 about Minimum Wage is equal to 73 % that have not been implemented properly and the rights of workers under the Law No. 13 of 2003 about Employment is equal to 66 % that has not been properly implemented.Keyword: Payment of Wages, Workers' Rights, Analysis